KAJIAN KONSENTRASI LARUTAN EFFEKTIVE MIKROORGANISME-4 (EM4) DAN MACAM MEDIA TANAM TERHADAP PERTUMBUHAN SEMAI PINUS (PINUS MERKUSII JUNGH ET DE. VRIESE) - Rahayu, Nandang; Mutaqin, Tatag (Jurnal Gamma, 2012)
Kajian Konsentrasi Larutan Effektive  Mikroorganisme-4 (Em4) Dan Macam Media Tanam Terhadap Pertumbuhan Semai Pinus (pinus merkusii jungh et de. Vriese)Nandang Rahayu1 & Tatag Mutaqin2Staf Pengajar Jurusan Kehutanan, Fakultas Pertanian PeternakanUniversitas Muhammadiyah Malang email : 1)nandang21@yahoo.com, 2)tatag.umm@gmail.comABSTRACTIntent and purpose of this study was conducted to determine the effect of solution concentration range of EM4 and growing media on seedling growth of pine (Pinus merkusii Jungh et.de Vriese). Materials research include soil and sand media, microorganisms effektive-4 (EM4), cow manure, chicken manure, goat manure, sawdust sengon and teak, pine seedlings 30 days old.The tools used in this study are poly as a media, hoes, hand sprayer, sliding term, rulers, scales analytic, ovens, cameras and stationery. This study used a randomized block design (RGD) factorial with three replications consisting of two factors: factor 1 is a medium (M) M1 = sand, top soil, cow manure (1:1:1), M2 = sand, top soil, chicken manure (1:1:1), M3 = sand, top soil, sawdust sengon (1:1:1), M4 = top soil, sheep manure, teak sawdust (1:1:1) . The second factor EM4 solution concentration solution Eo = without EM, E1 = 5 ml / liter, E2 = 10 ml / liter, E3 = 15 ml / liter.The analysis showed an interaction range between the concentration of microorganisms effektive-4 and the planting medium to high range of pine seedlings at 14 DAP to 91 DAP, stem diameter at age 14 to 21. While the wet weight and dry weight is not an interaction.Solution concentration of microorganisms effektive-4 (EM4) 10 ml / liter (E2) and the planting medium sand: top soil: cow manure (M1) tend to produce the best treatment than the treatment (M3E2) and (M4E2).Key word : Concentration, solution Affektive, Microorganisme-4, Semai Pinus